PENGARUH PENYAKIT PERIODONTAL SELAMA MASA KEHAMILAN TERHADAP JUMLAH TOTAL LEUKOSIT DAN HITUNG JENIS LEUKOSIT - Nuarita, Rusliyana; Praharani, Depi; Kusumawardani, Banun (STOMATOGNATIC- Jurnal Kedokteran Gigi, 2012)
The changes of hormonal during pregnancy can increase the hormones estrogen and progesterone. Increased estrogen and progesterone can cause excessive response in periodontal tissues so easily happen inflammation of the periodontal tissues. The most important aspects of the inflammation is the leukocyte reaction. The purpose of this study was to determine the effect of periodontal disease during pregnancy to the total number of leukocytes and leukocyte counts. Research procedures performed each trimester which includes examining periodontal index (PI) to assess the severity of periodontal disease and total leukocyte counts and leukocyte counts were taken from venous blood. The data obtained were analyzed with linear regression test. Statistical analysis showed that the higher the score PI will increase the total number of leukocytes. The conclusion of this study is periodontal disease during pregnancy may increase the total number of leukocytes and leukocyte counts.